2010
DOI: 10.1002/mrm.22675
|View full text |Cite
|
Sign up to set email alerts
|

Histogram analysis of the microvasculature of intracerebral human and murine glioma xenografts

Abstract: The purpose of this study is to examine the usefulness of histogram analysis combined with vessel size index (VSI) magnetic resonance imaging for the specific characterization of brain tumor microvasculature in a panel of six volume-matched glioma xenografts. Using a simple descriptive histogram analysis, significant differences of the mean tumoral VSI (P 5 0.0035 for 9L, P 5 0.008 for glioma mix, P 5 0.05 for C6), the 75th VSI percentile (P 5 0.003-0.075) as well as the 25th and median blood volume (BV) perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Histogram-derived parameters such as skewness, kurtosis, and percentiles have been found to be useful in differentiating between types of gliomas. 19 Other investigators found that rCBV histograms correspond with glioma grades, 20 and ADC histograms can stratify progression-free survival in GBM. 21,22 A similar technique has been used in DIPG to demonstrate significant intratumoral and interpatient mean diffusivity heterogeneity, 23 and shorter overall survival was found to be associated with increased ADC histogram skewness.…”
Section: Discussionmentioning
confidence: 96%
“…Histogram-derived parameters such as skewness, kurtosis, and percentiles have been found to be useful in differentiating between types of gliomas. 19 Other investigators found that rCBV histograms correspond with glioma grades, 20 and ADC histograms can stratify progression-free survival in GBM. 21,22 A similar technique has been used in DIPG to demonstrate significant intratumoral and interpatient mean diffusivity heterogeneity, 23 and shorter overall survival was found to be associated with increased ADC histogram skewness.…”
Section: Discussionmentioning
confidence: 96%
“…The histogram analysis not only describes statistical information but also provides a quantitative methodology for analyzing the nonsignificant changes upon imaging pixels data of tumor . For instance, some parameters of histogram analysis may be potential predictors of response to treatment as well as promising parameters for distinguishing tumor subtypes . During the past several decades, histogram approaches in diffusion MRI of PCa have drawn some researchers' attention .…”
Section: Discussionmentioning
confidence: 99%
“…With increasing advances in both high-resolution MRI and signal processing methods, histogram analysis of cancer MRI is more and more used. This methodology showed its usefulness for investigating the distributions of various tumour parameters such as permeability in dynamic contrast-enhanced MRI (DCE-MRI) ( Hayes et al , 2002 ; Padhani, 2002 ; Peng et al , 2012 ), vessel size index and blood volumes (VSI, CBV) ( Just, 2011 ; Burrell et al , 2012 ) and apparent diffusion coefficient (ADC) in diffusion MRI ( Downey et al , 2013 ).…”
Section: Tumour Heterogeneity: Methods Are Needed For An Appropriate mentioning
confidence: 99%